2019
DOI: 10.1038/s41591-019-0381-y
|View full text |Cite
|
Sign up to set email alerts
|

A clinically meaningful metric of immune age derived from high-dimensional longitudinal monitoring

Abstract: Immune responses generally decline with age. However, the dynamics of this process at the individual level have not been characterized, hindering quantification of an individual’s immune age. Here, we use multiple ‘omics’ technologies to capture population- and individual-level changes in the human immune system of 135 healthy adult individuals of different ages sampled longitudinally over a nine-year period. We observed high inter-individual variability in the rates of change of cellular frequencies that was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
348
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 364 publications
(375 citation statements)
references
References 39 publications
22
348
3
2
Order By: Relevance
“…We found strong enrichment of the signatures of youth and aging in the young and elderly adults, respectively (Figure 6A). The signature of youth had gene ontology terms for RNA metabolism whereas the signature of aging had terms for fatty acid metabolism and cytoskeletal regulation (Supplemental Figure 6B), in agreement with other signatures of aging (28).To further validate these signatures, we identified several published studies (13,(50)(51)(52) that generated whole-blood transcriptional profiles on adults under age 40 or over age 65 ( Supplemental Table 8). From these data, we performed differential expression analysis of young compared to elderly in multiple geographically distinct studies and again found robust enrichment for these signatures in the external datasets ( Figure 6B, Supplemental Figure 6C).…”
supporting
confidence: 57%
See 1 more Smart Citation
“…We found strong enrichment of the signatures of youth and aging in the young and elderly adults, respectively (Figure 6A). The signature of youth had gene ontology terms for RNA metabolism whereas the signature of aging had terms for fatty acid metabolism and cytoskeletal regulation (Supplemental Figure 6B), in agreement with other signatures of aging (28).To further validate these signatures, we identified several published studies (13,(50)(51)(52) that generated whole-blood transcriptional profiles on adults under age 40 or over age 65 ( Supplemental Table 8). From these data, we performed differential expression analysis of young compared to elderly in multiple geographically distinct studies and again found robust enrichment for these signatures in the external datasets ( Figure 6B, Supplemental Figure 6C).…”
supporting
confidence: 57%
“…To further validate these signatures, we identified several published studies (13,(50)(51)(52) that generated whole-blood transcriptional profiles on adults under age 40 or over age 65 ( Supplemental Table 8). From these data, we performed differential expression analysis of young compared to elderly in multiple geographically distinct studies and again found robust enrichment for these signatures in the external datasets ( Figure 6B, Supplemental Figure 6C).…”
Section: Age-related Differences Preferentially Revealed By Cd4 T Celmentioning
confidence: 99%
“…From these observations, it has been postulated that inflammation plays a critical role in regulating physiological aging (Franceschi and Campisi, 2014;Furman et al, 2017b). Furthermore, the well-established nine hallmarks of aging (Lopez-Otin et al, 2013); (1) genomic instability, (2) shortening telomere length, (3) epigenetic modifications, (4) loss of proteostasis, (5) deregulated nutrient sensing, (6) mitochondrial dysfunction, (7) cellular senescence, (8) stem cell exhaustion, and (9) altered intracellular communication, have all been shown to be caused, at least in part, by sustained systemic inflammation (Cavadas et al, 2016;Efeyan et al, 2015;Grivennikov et al, 2010;Hunter et al, 2007;Jurk et al, 2014;Lasry and Ben-Neriah, 2015;Nathan and Cunningham-Bussel, 2013;Oh et al, 2014;Thevaranjan et al, 2017;Alpert et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, by longitudinal monitoring of healthy individuals we are learning how newborn immune systems are shaped early in life 9 , and how immunological changes associated with aging manifest itself and affect disease risks in the elderly 10 .…”
Section: Systems Immunology Involves Simultaneous Analyses Of All Immmentioning
confidence: 99%